Variant origin of the left vertebral artery from a vertebro-subclavian trunk associated with an unusual branch arising from the brachiocephalic trunk. - Satheesha BN,; Sirasanagandla SR,; Surekha DS,; Deepthinath R,; Sudarshan S,; Raghu J, (Department of Surgery, UKM Medical Centre, 2014)
Variant origin of the left vertebral artery (LVA) from the arch of aorta is well documented in the literature. Involvement of complex sequential developmental steps in the aortic arch formation results in different patterns of origin of LVA. Morphological variations in the LVA are thought to alter the cerebral hemodynamics and can cause the cerebral dysfunction. Knowledge of the morphological variations of the LVA is useful while performing the head and neck and thoracic surgeries. We here report one of the extremely rare patterns of the LVA origin, in a male cadaver aged about 65 years. LVA and left subclavian artery (LSA) arose as a common vertebro-subclavian trunk from the convexity of the aortic arch. Further, brachiocephalic trunk (BT) gave an unusual artery from its anterior surface. This artery divided into thymic and tracheal branches. Variant origin of thymic branch may be crucial during imaging and thymectomy procedures.